Nānā I Ke Kumu: Look to the Source - Silva, Noenoe (Te Kaharoa, 2009)
Many indigenous peoples have been re-claiming and revitalising our ancestors’ languages and cultural practices. Now it is time to also research, re-think, and re-value their political thought and practices. This has been difficult because it is one of the areas, along with language and religion, which has been the most disparaged through colonialism. This article explores ways in which this re-claiming and revitalising is taking place.